BAGAIMANA PENGGUNAAN DANA DESA UNTUK PEMBERDAYAAN MASYARAKAT DESA? - Monika, Agnes; Razak, Andi Rosdianti; Malik, Ihyani (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to find out how the priority is the use of village funds in community empowerment in Turatea Village. This type of research uses qualitative methods. Data sources consist of primary data obtained through interviews, and secondary data taken from documents, notes, reports, and official archives. The results of the research show 1) The Village Government of the Turatea office has allocated priorities for the Village fund budget with previous planning, so that the planning produces a program in the village of Turatea. 2) Implementation of the allocation of funds for the Turatea Village, Jeneponto Regency, is allocated in the administration of the Village government according to the existing fields in the Turatea Village government. 3) Arrangements are made in accordance with (SOP). 4) There is a form of reporting on the allocation of village budget funds to empower the Turatea Village community, amounting to IDR 211,500,000. 5). There is accountability from the Turatea Village Government which can be accessed.